2013
DOI: 10.1055/s-0033-1349107
|View full text |Cite
|
Sign up to set email alerts
|

Small-Sided Game Training Improves Aerobic Capacity and Technical Skills in Basketball Players

Abstract: The aim of this study was to compare the effects of 2 training interventions based on small-sided games (SGG) and high-intensity interval training (HIT) on physical and technical performance of male junior basketball players. A secondary objective was to investigate if these effects were similar in starting and bench players. 18 players participated in a pre-testing session, 6-weeks intervention period and a post-testing session. Pre- and post-sessions involved assessments of aerobic fitness, repeated sprint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
2
31

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(137 citation statements)
references
References 27 publications
9
87
2
31
Order By: Relevance
“…However, the present study analysed only the acute technical responses in relation to the number of players involved, while a possible improvement in pass and shot skills effectiveness could be assessed during a ball-drill training period. In fact, a beneficial effect of SSG training on defensive and shooting skills has been reported in a study focusing on SSG training interventions in basketball (Delextrat & Martinez, 2014), despite those skills being assessed only in time-based skills tests and not in a game-based situation. Therefore, future studies should investigate the effect of SSGs training interventions, verifying their effect in official games or game-based conditioning drills.…”
Section: Number Of Playersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present study analysed only the acute technical responses in relation to the number of players involved, while a possible improvement in pass and shot skills effectiveness could be assessed during a ball-drill training period. In fact, a beneficial effect of SSG training on defensive and shooting skills has been reported in a study focusing on SSG training interventions in basketball (Delextrat & Martinez, 2014), despite those skills being assessed only in time-based skills tests and not in a game-based situation. Therefore, future studies should investigate the effect of SSGs training interventions, verifying their effect in official games or game-based conditioning drills.…”
Section: Number Of Playersmentioning
confidence: 99%
“…Recently, a number of research papers specifically investigated basketball training in the form of ball-drills (Atli, Koklu, Alemdaroglu, & Unver Kocak, 2013;Castagna, Impellizzeri, Chaouachi, Ben Abdelkrim, & Manzi, 2011;Delextrat & Martinez, 2014). Separately, these researchers reported that ball-drills were useful tools for basketball aerobic training showing how selected variables can influence the ball-drills workload.…”
Section: Introductionmentioning
confidence: 99%
“…Small-sided games (SSGs) are widely used by basketball coaches in an attempt to simultaneously develop technical and tactical skills under high physical loads (Atl, Koklu, Alemdaroglu, & Kocak, 2013;Castagna, Impellizzeri, Chaouachi, Ben Abdelkrim, & Manzi, 2011;Delextrat & Martinez, 2014;Klusemann, Pyne, Foster, & Drinkwater, 2012;McCormick et al, 2012;Sampaio, Abrantes, & Leite, 2009). Previous research suggest that physiological (heart rate, HR) and perceptual (rating of perceived exertion, RPE) demands of SSGs can be manipulated by changing the size of the court and the number of players involved.…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de estudios fueron llevados a cabo en situaciones de medio campo (15x14m) y todo el campo (28x15m; Atli y col., 2013; Castagna y col., 2011; Conte y col., 2016; Conte y col., 2015; Dehesa y col., 2015; Klusseman y col., 2012; Montgomery y col., 2010), aunque hay algunos estudios (Delextrat y Martinez, 2014;Delextrat y Kraiem, 2013) que también han dividido el campo en dos partes en vertical (28x7.5m; Tabla 1). No obstante, solo se dispone de dos estudios que contrastaron de forma directa la FC y la intensidad del juego en situaciones de oposición en medio y todo el campo (Atli y col., 2013; Klusseman y col., 2012).…”
Section: Resultados Y Discusiónunclassified